2019
DOI: 10.17559/tv-20181029214825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solar Radiation on Current-Carrying Capacity of PVC-insulated Power Cables – the Numerical Point of View

Abstract: Power cables are usually buried in the soil, which results in their relatively high current-carrying capacity. However, there are cases in which the starting/final section of a cable line runs along a pole of an overhead power line. Power cables can be directly exposed to solar radiation then, and this negatively influences their currentcarrying capacity as well as estimated life of the cables' insulation. An analysis of thermal phenomena in PVC-insulated low-voltage power cables, exposed to solar radiation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…At the same time, the heating of the DC and AC cables, which are an integral part of the PV power plant, is also evident. It is clear that the temperature of the cable insulation depends on the insolation, the temperature of the surrounding air, but also the generation of heat inside the cable itself [42]. It can be observed that the influence of the measured wind speeds on the panel and cable temperature is very small, which is consistent with the results of Mayer and Grof [43].…”
Section: High Temperaturessupporting
confidence: 86%
“…At the same time, the heating of the DC and AC cables, which are an integral part of the PV power plant, is also evident. It is clear that the temperature of the cable insulation depends on the insolation, the temperature of the surrounding air, but also the generation of heat inside the cable itself [42]. It can be observed that the influence of the measured wind speeds on the panel and cable temperature is very small, which is consistent with the results of Mayer and Grof [43].…”
Section: High Temperaturessupporting
confidence: 86%